2020
DOI: 10.1101/2020.02.24.962449
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

shRNA Glut-1 inhibits cell viability, apoptosis and migration of laryngeal carcinoma HEp-2 cells through regulating Beclin-1-mediated autophagy

Abstract: Objective: Glut-1 is a key regulator in the process of glucose uptake. Previous studies have shown that Glut-1 affects autophagy. However, it is unclear whether there is a correlation between Glut-1 and autophagy in the progression of laryngeal carcinoma.This study was performed to investigate the role of Glut-1 in the development of laryngeal carcinoma.Methods: A stable HEp-2 cell model was constructed by Glut-1 and Beclin-1 shRNA lentiviral infection. The autophagosome was measured by transmission electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Given such intimacy between various miRNAs and GLUT isoforms, there is a strong logic to utilize them in therapeutic applications. Similarly, a study on the role of MiR-218 and MiR340 in the expression of GLUT1 is demonstrated in oral squamous cell carcinoma (OSCC) ( Xu et al, 2018 ; Wang et al, 2020 ; Shiah et al, 2021 ). Combinatorial use of miRNAs with other conventional GLUT1 inhibitors is also needed to be explored to circumvent GLUT at both gene expression and protein function levels.…”
Section: Additional Approachesmentioning
confidence: 97%
See 1 more Smart Citation
“…Given such intimacy between various miRNAs and GLUT isoforms, there is a strong logic to utilize them in therapeutic applications. Similarly, a study on the role of MiR-218 and MiR340 in the expression of GLUT1 is demonstrated in oral squamous cell carcinoma (OSCC) ( Xu et al, 2018 ; Wang et al, 2020 ; Shiah et al, 2021 ). Combinatorial use of miRNAs with other conventional GLUT1 inhibitors is also needed to be explored to circumvent GLUT at both gene expression and protein function levels.…”
Section: Additional Approachesmentioning
confidence: 97%
“…Similarly, the use of shRNA to GLUT1 was observed to show promising outcomes in colon cancer cells ( Bai et al, 2019 ). Wang et al (2020) demonstrated that shRNA inhibits the survival of laryngeal carcinoma HEP2 cells via beclin-1-associated autophagy. shRNA to GLUT1 is also reported to effectively block glucose uptake in various cancer cell lines ( Pliszka and Szablewski, 2021 ).…”
Section: Additional Approachesmentioning
confidence: 99%